2001
DOI: 10.1002/lsm.1124
|View full text |Cite
|
Sign up to set email alerts
|

Does new photosensitizer improve photodynamic therapy in advanced esophageal carcinoma?

Abstract: Despite the limitations of a non-randomized study, photosensitzation with Photosan seems to be more effective in PDT of advanced esophageal carcinoma compared to ALA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 22 publications
1
34
0
1
Order By: Relevance
“…Meta-analysis was not possible due to heterogeneity between the trials. All trials reported morbidity results, seven reported on mortality [113][114][115][116][117][118][119] and four reported on QoL outcomes. [115][116][117][118] Only two of the studies reported resource use, both in terms of days of hospitalisation.…”
Section: Results Of Effectiveness (Palliative Intent)mentioning
confidence: 99%
See 4 more Smart Citations
“…Meta-analysis was not possible due to heterogeneity between the trials. All trials reported morbidity results, seven reported on mortality [113][114][115][116][117][118][119] and four reported on QoL outcomes. [115][116][117][118] Only two of the studies reported resource use, both in terms of days of hospitalisation.…”
Section: Results Of Effectiveness (Palliative Intent)mentioning
confidence: 99%
“…[107][108][109][110][111][112][113][114][115][116][117][118][119] Three studies were available only as abstracts, 107,110,111 the rest were published as full papers. In a small number of trials, the presented data did not appear to entirely support the authors' conclusions; this has been indicated in the data extraction tables.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations